Affinity-Enhanced CTC-Capturing Hydrogel Microparticles Fabricated by Degassed Mold Lithography - Nak Jun Lee; Sejung Maeng; Hyeon Ung Kim; Yoon Ho Roh; Changhyun Hwang; Jongjin Kim; Ki-Tae Hwang; Ki Wan Bong (Journal of Clinical Medicine, 2020)
Technologies for the detection and isolation of circulating tumor cells (CTCs) are essential in liquid biopsy, a minimally invasive technique for early diagnosis and medical intervention in cancer patients. A promising method for CTC capture, using an affinity-based approach, is the use of functionalized hydrogel microparticles (MP), which have the advantages of water-like reactivity, biologically compatible materials, and synergy with various analysis platforms. In this paper, we demonstrate the feasibility of CTC capture by hydrogel particles synthesized using a novel method called degassed mold lithography (DML). This technique increases the porosity and functionality of the MPs for effective conjugation with antibodies. Qualitative fluorescence analysis demonstrates that DML produces superior uniformity, integrity, and functionality of the MPs, as compared to conventional stop flow lithography (SFL). Analysis of the fluorescence intensity from porosity-controlled MPs by each reaction step of antibody conjugation elucidates that more antibodies are loaded when the particles are more porous. The feasibility of selective cell capture is demonstrated using breast cancer cell lines. In conclusion, using DML for the synthesis of porous MPs offers a powerful method for improving the cell affinity of the antibody-conjugated MPs.